Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 6593 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Didymodon tophaceus (Brid.) Lisa", "HasGeospatialIssue is false", "Geometry POLYGON((152.23 -70.38,152.23 85.05,-126.91 85.05,-126.91 -70.38,152.23 -70.38))" ] } The dataset includes 6593 records from 83 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0007026-160623103540712/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences